WALANT Hand Surgery Does Not Require Postoperative Opioid Pain Management. Issue 1 (July 2021) - Dar, Qurratul-Ain; Avoricani, Alba; Rompala, Alexander; Levy, Kenneth H.; Shah, Neil V.; Choueka, David; White, Colin M.; Koehler, Steven M.
Abstract : Background: Currently, opioids are the standard of care for postoperative pain management. Avoiding unnecessary opioid exposure in patients is of current interest because of widespread abuse. Methods: This is a prospective cohort study in which wide-awake, local anesthesia, no-tourniquet (WALANT) technique was used for 94 hand/upper extremity surgical patients and compared to patient cohorts undergoing similar procedures under monitored anesthesia care. Patients were not prescribed opioids postoperatively but were instead directed to use over-the-counter pain relievers. Pain scores on a visual analogue scale were collected from patients preoperatively, and on postoperative days 1 and 14. WALANT visual analogue scale scores were compared to those of the two patient cohorts who either did or did not receive postoperative opioids after undergoing similar procedures under monitored anesthesia care. Electronic medical records and New York State's prescription monitoring program, Internet System for Tracking Over-Prescribing, were used to assess prescription opioid-seeking. Information on sex, age, comorbidity burden, previous opioid exposure, and insurance coverage was also collected. Results: Decreased pain was reported by WALANT patients 14 days postoperatively compared to preoperatively and 1 day postoperatively, with a total group mean pain score of 0.37. This is lower than mean scores of monitored anesthesia care patients with and without postoperative opioids. Only two WALANT patients (2.1 percent) sought opioid prescriptions from outside providers. There was little evidence suggesting factors including sex, age, comorbidity burden, previous opioid exposure, or insurance status alter these results. Conclusion: WALANT may be a beneficial technique hand surgeons may adopt to mitigate use of postoperative opioids and reduce risk of abuse in patients. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.